Management of results of intellectual activity: economical and legal aspects - A. Y. Shkarin (Путеводитель предпринимателя)
In article the questions connected with management of results by intellectual property are considered, the analysis of existing legal base on this subject is submitted, and also recommendations about the taxation and accounting support of the organizations which are engaged in intellectual property are made.